2012
DOI: 10.1177/1533317512442999
|View full text |Cite
|
Sign up to set email alerts
|

Which Cholinesterase Inhibitor is the Safest for the Heart in Elderly Patients With Alzheimer’s Disease?

Abstract: It was demonstrated that none of the 3 ChEIs were associated with increased negative chronotropic, arrhythmogenic, and hypotensive effects for the elderly patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
2
28
0
1
Order By: Relevance
“…Regarding outcomes, hypertension was defined according to objective measurement in 9 studies. [13][14][15][16][23][24][25][26]33 Bradycardia and heart rate changes were evaluated according to objective measurement in 17 studies, 13,[15][16][17]19,[22][23][24][25][26][27][28][29][30][31]33,34 and one study reported data on bradycardia from a database. 32 After a median follow-up of 24 weeks (range 3-463 weeks), AChEI use was associated with a higher proportion of hypertension in 7 studies compared to baseline (1,573 individuals, 4%, 95% CI52-8%, p<.001, I 2 547%) and bradycardia in 12 studies (13,703 participants, 2%, 95% CI51-6%, p<.001, I 2 598%).…”
Section: Longitudinal Studies Reporting On Changes Over Time In CV Oumentioning
confidence: 99%
“…Regarding outcomes, hypertension was defined according to objective measurement in 9 studies. [13][14][15][16][23][24][25][26]33 Bradycardia and heart rate changes were evaluated according to objective measurement in 17 studies, 13,[15][16][17]19,[22][23][24][25][26][27][28][29][30][31]33,34 and one study reported data on bradycardia from a database. 32 After a median follow-up of 24 weeks (range 3-463 weeks), AChEI use was associated with a higher proportion of hypertension in 7 studies compared to baseline (1,573 individuals, 4%, 95% CI52-8%, p<.001, I 2 547%) and bradycardia in 12 studies (13,703 participants, 2%, 95% CI51-6%, p<.001, I 2 598%).…”
Section: Longitudinal Studies Reporting On Changes Over Time In CV Oumentioning
confidence: 99%
“…In summary, although uncommon, ACHI therapy appears to be associated with about a 1.5-2 fold risk of developing bradycardia. The vast majority of patients receiving ACHIs will have normal ECGs and no significant hemodynamic changes [18][19][20]. There is insufficient data to determine whether there are differences between the individual class members of ACHIs and the risk of bradycardia as most of the data relate to donepezil therapy [19].…”
Section: Bradycardiamentioning
confidence: 99%
“…The remarkable thing about this case is the development of asymptomatic bradycardia due to rivastigmine use. Although ChEIs are safe for the cardiac system, a limited number of case reports indicate development of atrioventricular block during rivastigmine therapy. In one of them, the relationship between development of third‐degree atrioventricular block and rivastigmine therapy could not be demonstrated definitely because cardiac biomarkers were higher than normal in both cases and ischemic etiology could not be fully clarified .…”
Section: Discussionmentioning
confidence: 99%
“…Although the brain is the main target organ of rivastigmine therapy, cardiac muscle tissue, which is rich in cholinesterase, could be adversely affected. Potential cardiac adverse events, including bradycardia, cardiac block, and prolonged QT, may result from vagotonic effects of ChEIs, but a limited number of studies have demonstrated that ChEIs, including rivastigmine, are safe for the cardiac system . Nevertheless, there are a few case reports of rivastigmine‐induced bradycardia in the literature .…”
mentioning
confidence: 99%